Value and ethical objectives of the children's theater (9-12) years (Journal of the College of Basic Education, 2022)
Children's theater is one of the most important educational and recreational means that contribute to the development of the child mentally, intellectually, socially, psychologically, scientifically and morally. The important stages in a child's life and in building his personality, which is the stage of free imagination, free play, adventure and heroism, whose future effects remain and show clear on the individual's personality, patterns of behavior, habits, traditions, inclinations and attitudes towards himself and towards others in the surrounding environment.